Kepemimpinan Pelayan Mengajarkan Teologi Memberi di Kalangan Pekerja Migran Indonesia di Gereja Lokal Malaysia - Joni Manumpak Parulian Gultom (DIEGESIS: Jurnal Teologi Kharismatika, 2022)
Indonesian migrant workers in Malaysia are the main source of the country's huge foreign exchange income. Within the church, their number alone is relatively large spread across the peninsula. The Lord's Church serves them as souls in need of strength and discipleship in the faith. Church leadership becomes important in directing the life of faith and also in the management of future lives. In addition to making them obedient people from the example of servant leaders, the church is also responsible for bringing them to love their fellow human beings with their finances in terms of giving. The question is first, what is the correct method of teaching the theology of giving to migrant workers? And what kind of servant leadership strategy do you expect? Research method with qualitative description. The purpose of the study is to describe the basis and pattern of Biblical giving and to explain appropriate servant leadership strategies for Indonesian migrant workers in Malaysia AbstrakPekerja migran Indonesia di Malaysia menjadi sumber utama pemasukan devisa negara yang sangat besar. Dalam gereja, jumlah mereka sendiri terbilang relative besar yang tersebar di semenanjung. Gereja Tuhan melayani mereka sebagai jiwa yang perlu kekuatan dan pemuridan dalam iman. Kepemimpinan gereja menjadi penting dalam mengarahkan kehidupan iman dan juga management kehidupan masa depan. Selain menjadikan mereka umat yang taat dari keteladanan pemimpin yang melayani, gereja juga bertanggung jawab untuk membawa mereka dapat mengasihi sesama manusia dengan keuangan mereka dalam hal memberi. Pertanyaan nya dalah pertama, bagaiamana metode mengajarkan teologi memberi yang benar buat para pekerja migran? Dan strategi kepemimpinan pelayan seperti apa yang di harapkan? Metode penelitian dengan dekripsi kualitatif. Tujuan penelitian untuk menggambarkan kepemimpinan di gereja sangat berpengaruh memberikan andil dalam mendorong umat untuk memberi.